Evaluating the role of local climate change on reduced freshwater availability at the Peace-Athabasca Delta using paleolimnology - Brown, Kathleen (University of Waterloo, 2022)
Abundant small, shallow lakes across northern freshwater landscapes are particularly sensitive to alteration of hydrological processes, which makes them vulnerable to multiple potential stressors. At the Peace-Athabasca Delta (PAD; Treaty 8; northeastern Alberta), a Ramsar Wetland of International Importance, lake drying and associated ecological consequences present a critical water security concern due to potential stressors such as climate change and upstream industrial projects. Hydrometric, paleolimnological, and other studies have identified multiple mechanisms that have contributed to lake drying to varying degrees during the past century including upstream river regulation, climate driven changes in flood frequency and magnitude, geomorphic change in distributary flow, and contraction of Lake Athabasca from low lying areas of the PAD. The many mechanisms at play within the delta have made it challenging to distinguish the relative role of local hydroclimatic processes and conditions (i.e., catchment runoff, precipitation, evaporation, relative humidity) on lake drying at the PAD. This study focuses on identifying intervals when local hydroclimate has increased evaporation of lakes during the past ~400 years using paleolimnological analysis at four hydrologically isolated lakes adjacent to the PAD. Then, to determine the relative role of local hydroclimate in lake drying at the PAD, paleohydrological records from the study lakes were compared to paleohydrological data and contemporary hydrological monitoring records from perched basins within the PAD that exhibit recent drying. Specific intervals of interest include previously identified episodes of drying in the PAD during the Little Ice Age (LIA; 1600-1900 CE) and during the twentieth (1900-2000 CE) and twenty-first (2000-2019 CE) centuries. Lake water oxygen isotope composition was reconstructed from cellulose oxygen isotope composition (cellulose-inferred ẟ18Olw). Stratigraphic intervals of cellulose-inferred ẟ18Olw values > 1 standard deviation ...